Dynamic Surface Chemistry of Catalysts in Oxygen Evolution Reaction. Issue 7 (9th May 2021) - Kou, Zongkui; Li, Xin; Zhang, Lei; Zang, Wenjie; Gao, Xiaorui; Wang, John
Abstract : Electrocatalytic oxygen evolution reaction (OER) is a crucial anode reaction where electrocatalysts are the key elements and their dynamic surface chemistry runs throughout the entire process. Herein, we examine the latest advances and challenges in understanding of the dynamic surface chemistry of OER electrocatalysts. There are electrochemical origin and driving force for the dynamic surface nature, where several processes can take place either concurrently or sequentially, including reconstruction (i.e., phase formation/transformation, morphological change, and compositional change), vacancy generation and filling/refilling, and the intermediate adsorption–desorption process on catalytic surface. These dynamic surface processes of OER catalysts are impacted by not only the reaction and service conditions, including the (local) pH and its gradient distribution, applied potential, types and concentration of exotic ions and external fields on top of the nature of catalysts/precatalysts, but also their interactions. Due to the local, time‐dependent and instant nature, there are considerable challenges in tracing, modelling and understanding of the complete dynamic surface chemistry of catalysts in OER, by means of ex situ, in situ and operando experimental investigations. Therefore, computational studies and dynamic simulations help provide key insights in future pursuits, where there is critical need for a multiscale computational modelling approach encompassing all these aspects. Abstract : Dynamic surface chemistry of catalysts dominates the actual oxygen evolution reaction (OER) process and performance. It involves either the reversible or irreversible dynamics, or both. There are strong effects of electrochemical servicing environments and external fields on OER. Both operando experiments and theoretical insights are particularly important.